(untitled) (Bulletin of Kharkiv National University of Internal Affairs, 2025)
The article examines the current role of territorial communities as active actors in Ukraine’s cybersecurity system. It focuses on the educational, monitoring and legal components of communities’ activities in the digital environment, which are becoming key factors in shaping the state’s cyber resilience. It is emphasised that with the development of e-government, digital services and online communications, communities can no longer remain passive users of technology, but must develop their own culture of security, responsibility and self-defence skills in cyberspace. It is argued that ensuring cybersecurity at the community level is integrated and covers several interrelated areas: technical protection of information systems, public education in the field of cyber hygiene, monitoring of digital threats, and the responsibility of officials for violations of information security rules. Particular attention is paid to the role of communities in spreading knowledge regarding safe online behaviour, preventing cybercrime, and countering disinformation and fake news. It is emphasised that it is at the local level that the population first interacts with the state’s digital services, so communities are effectively the first line of defence in the field of cybersecurity. An important aspect of the study is the issue of legal and organisational responsibility. It is noted that local authorities should develop and implement local cyber security policies, create incident monitoring systems, and maintain cooperation with national cyber security structures such as CERT-UA, the Ministry of Internal Affairs of Ukraine, and the Security Service of Ukraine. A three-level model of interaction is proposed: education – monitoring – responsibility, which ensures not only the technical but also the social stability of the community’s digital environment. It is concluded that the development of cyber culture at the community level is a necessary condition for building a national security system. Without the conscious participation of citizens, educational institutions, businesses, and local governments, it is impossible to create effective protection for the information space. It is emphasised that communities are not only objects of cyber protection, but also full-fledged subjects capable of acting proactively, introducing modern standards of digital security, ensuring public trust in the digital state and increasing the overall level of national cyber resilience.